Metakognisi siswa dalam pemecahan masalah matematika ditinjau dari gaya belajar - Roni Irwansyah, Roni Irwansyah; Sofyan Mahfudy, Sofyan Mahfudy (Jurnal of Math Tadris, 2021)
The purpose of this study was to describe students' metacognition in solving mathematical problems in terms of learning styles. The method in this research is descriptive qualitative. The subjects in this study were students. Data collection techniques used are questionnaires, tests and interviews. The analysis technique used consists of three components, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are differences in students' metacognition processes, namely: a) The metacognitive process of visual students is moderate. It can be seen when students plan, use information from problems to answer questions well. When monitoring, students check the information obtained when solving a given problem. When evaluating, students are incomplete in writing the final results at the conclusion. b) The process of auditory students' metacognition is lacking. It can be seen when students plan, do not draw and write down the information provided. When monitoring, students check the information obtained when solving a given problem. When evaluating, students re-check the completion that has been done but the final result is incomplete. c) High kinesthetic students' metacognition process. It can be seen when students plan, explain and write down what is in the problem, describe and write down what is known and asked about the problem. When monitoring, students choose the concept of completion correctly, apply the information obtained to concepts that have been thought out and are thorough in answering questions and believe that the answer process is correct. When evaluating, accuracy in writing the final results that have been done rightly and correctly.